(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article comparatively analyzes the image of night in Eastern and Western literature as well as its interpretations connected with human psychology, loneliness, inner suffering, and existential experiences. During the research, the symbolic-aesthetic, philosophical, and psychological functions of the night motif are revealed. In Eastern literature, night is mainly interpreted as a space of divine contemplation, spiritual purification, and inner reflection, whereas in Western literature it is associated with absurdity, spiritual emptiness, and the ontological loneliness of the individual. Based on the theory of existentialism and the methods of comparative literary studies, the article highlights the artistic and philosophical essence of the image of night.